Deciphering the Role of Stay-Green Trait to Mitigate Terminal Heat Stress in Bread Wheat - Sadia Latif; Liping Wang; Jahangir Khan; Zeshan Ali; Sunish Kumar Sehgal; Md Ali Babar; Jianping Wang; Umar Masood Quraishi (Agronomy, 2020)
The present study aimed to reveal the impact of the stay-green trait in bread wheat under terminal heat stress. Field experiments (early and late sowing; for two consecutive years) were conducted to investigate the influence of terminal heat stress on the morpho-physiological traits in different stay-green types i.e., non-stay-green, moderately non-stay-green, moderately stay-green, and stay-green. In addition, the greenhouse experiment was performed to dissect the stay-green trait in functional stay-green, non-functional stay-green, and non-stay-green genotypes. The results of the field experiments confirmed that genotypes exhibiting the stay-green trait have a significantly high chlorophyll content, normalized difference vegetative index, grain yield, biological yield, kernel weight, and low canopy temperature under control and heat stress conditions. In the greenhouse experiment, functional stay-green and non-functional stay-green genotypes showed a high chlorophyll content and photochemical efficiency, whereas biological yield and grain yield showed a significant relation with the functional stay-green genotype under control and terminal heat stress treatments. The sequencing and expression analysis of chlorophyllide a oxygenase (CaO), light-harvesting complex (Cab), stay-green (SGR), and red chlorophyll catabolite reductase (RCCR) in functional stay-green, non-functional stay-green, and non-stay-green genotypes revealed variations in the exons of CaO and RCCR; and significant difference in the regulation of CaO and Cab at 7 days after anthesis under terminal heat stress. This study confirms that genotypes displaying the stay-green trait can aid wheat breeders to cope with increasing temperature in the impending decades.